Oxisol quality indicators related to degradation of pastures - Lisbôa, Fabrício Marinho; donagemma, guilherme kangussu; Burak, Diego Lang; Passos, Renato Ribeiro; Mendonça, Eduardo de Sá (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to select the soil quality indicators more related to pasture degradation and to establish the limits of the different degradation levels using these indicators. Five pasture areas on an Oxisol were selected in the medium third of the slope, with different levels of visual degradation,considering the following variables: loss of vigor, presence of weeds, exposed bare soil, and erosion. Soil cover was evaluated, and soil samples were collected at the 0.00–0.05, 0.05–0.10, and 0.10–0.20-m soil depths, for physical, chemical, and organic matter analyses. Differently from the visual classification, the cluster analysis of the cover variables only indicated two degradation levels: low to moderate and high to very high, with classification percentage above 87% in the discriminant analysis, in which bare soil was the most assertive variable for discriminating the degradation levels. Light organic matter and the Ca+Mg component were the indicators most related to pasture degradation indices at 0.00–0.05 m; while potassium content was the indicator most related to those indices at the 0.05–0.10 and 0.10–0.20-m soil depths.
Keywords: Urochloa; vegetation cover; soil degradation; light organic matter